Circular Economy Breakthrough: Converting Used Cooking Oil Into Sustainable Biodiesel - YOKO, BUDI; FURQON, FURQON (JEJAK, 2025)
Used cooking oil is a household waste that has not yet been optimally managed, potentially leading toeconomic losses and environmental pollution. This study aims to analyze the behavior of housewives inBanyumas District in utilizing used cooking oil, identify the potential for developing biodiesel from usedcooking oil, and formulate strategies and roles for relevant stakeholders to optimize used cooking oilmanagement. The methodology employed in this research is mixed-method, utilizing primary data fromsurveys and secondary data from various related studies and publications. The analysis reveals that mosthousewives in Banyumas directly dispose of used cooking oil without prior processing. Adopting a circulareconomy approach in converting used cooking oil into biodiesel can prevent pollution and provide asustainable alternative energy source. This practice can also raise public awareness about environmentalpreservation, promote responsible consumption, and create additional income and green jobs.Implementing this policy requires collaboration from various stakeholders, including the government,academics, business actors, the community, and the media